Indirect Method for Determination of Paracetamol in Pure and Pharmaceutical Drugs using CFIA with Homemade Ayah 3SBGRX3-3D Solar Cell Microphotometer Analyzer - Nagam S. Turkey Al-Awadie1, Marwah A. Kadhim Al-banaa2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A method is described for the determination of paracetamol(based on the formation of a orange-reddish color species by reduction of Fe(III) to Fe(II) by paracetamol and then reacted with 1,10-phenanthroline) in the range 0.001-0.09mMol.L-1 (r =0.9801, r2 = 0.9606 , and R2% = 96.06) with a detection limit (LOD) 21.77ng/160?L(3SB)(S/N=3) and with RSD% for 0.01 and 0.07mMol.L-1 less than 1 % (n=6). The method was applied successfully for determination of paracetamol in pharmaceuticals formulation. Analysis of drugs used the standard additions method via the individual t-test. The results showed a significant., difference between the quoted..value of each company. with calculated t-test at 95% confidence(?=0.05) from new method.